Perancangan Sistem Informasi Pemesanan Produk Olahan Makanan UMKM Dengan Metode FIFO Berbasis Android - Nurul Asyilah; Suendri Suendri (Universitas Negeri Padang, 2023)
The development of the current era will always be followed by increasingly modern technological developments so that this will affect the life of individuals or groupsTechnology also helps MSMEs (Micro, Small and Medium Enterprises) to run business units owned by individuals or few people by generating certain revenues and profits. Mine Cakery is one of the SMEs in the city of Medan. Mine Cakery is a business that sells cakes or bread which is located at Jl. Aluminum 1 Tanjung Mulia. Mine Cakery In carrying out its business, it makes pre-order options for several orders, such as Birthday Cake, Wedding Cake etc. However, in the ordering process, the owner of the mine cake shop has difficulty processing orders when customers pre-order and there are too many orders, making it easy for the Mine Patisserie to determine which order to serve first. After the above issue, we need an Android-based application that will be used to process pre-orders. The application will be developed using the FIFO (First In First Out) method. Android-based applications are implemented using the Kotlin programming language and data is stored in the firebase database where the development method is Rapid Application Development. The research results will address the needs of Minecake and the pre-ordering process can be carried out systematically using the FIFO method